Fuzzy Delphi Analysis for Pedagogical Innovation Model (INO-PED) on Spiritual Element - Muhammad Noor Abdul , Aziz; Mohd Yusoff, Nurahimah; Sobri Shuib, Ahmad; Syed Idrus, Syed Khalid; Khairul Nuzul Hassan, Mohd; Siraj, Saedah; Nidzam Yaakob, Muhammad; Irhash Ahmad Puad, Mohd (Universitas Serambi Mekkah, 2024)
Situated within the ambit of the Malaysian Ministry of Education's national education action plan, this study addresses a conspicuous void in understanding teachers' implementation of innovative pedagogy (Ino-Ped). Employing a robust quantitative approach, the research meticulously examines the spiritual construct within Ino-Ped. The study engaged 18 experts encompassing diverse educational backgrounds, including professionals from Public Institutions of Higher Learning, Institutes of Teacher Education, and schools. A survey featuring items pertinent to the spiritual construct was subjected to Fuzzy Delphi analysis, a method employed to gauge expert consensus. The analysis revealed a noteworthy consensus of over 75% among experts regarding the integration of spiritual development within Ino-Ped. Furthermore, the study identified nine specific items associated with the spiritual construct that met the predefined threshold (d ≤ 0.2). These items were subsequently prioritized based on expert recommendations, providing valuable insights for further exploration. The study's findings underscore the paramount importance of incorporating spiritual values into pedagogical practices, contributing to an enriched teaching and learning environment. Beyond this immediate impact, the study establishes a structured framework that holds implications for future research endeavors and practical applications within the expansive domain of innovative pedagogy.